Development and Proposal of a Scale for Measuring the Image of Touristic Destinations (Imatur) [Desarrollo y Propuesta de Una Escala Para Medir la Imagen de Los Destinos Turísticos (Imatur)] - Marinao-Artigas, E (Fundacao Escola de Comercio Alvares Penteado, 2012)
Image plays an important role in the process of choosing a touristic destination. In view of its importance, the purpose of this study is to propose a valid, reliable and dimensional scale of measurement that allows measuring touristic destinations images. To achieve this objective, a methodology was developed in different stages, which includes building a scale with a range of content validity and analyzing their psychometric properties by means of different statistical methods, parametric and nonparametric. To develop this analysis, 750 people were surveyed in samples, in proportion to the touristic destinations visited in Chile. The results showed a scale to measure the image of a touristic destination, made up of cognitive perception, affective evaluation, and by functional, symbolic and hedonistic benefits. This study provides to different groups of interest relevant information regarding the factors that make up the image, and are the basis to achieve a better perception of the touristic destination. © FECAP.